HUBUNGAN MOBILISASI DINI DENGAN PROSES INVOLUSI UTERUS PADA IBU POST SECTIO CAESAREA DI RUMAH SAKIT UMUM SEMBIRING DELI TUA KABUPATEN DELI SERDANG SUMATERA UTARA TAHUN 2026 - SHINTA ANDRIA CHAIRANI; Marlen Sadrina Sitepu (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2026)
This study aims to analyze the relationship between early mobilization and uterine involution in post-cesarean section mothers at RSU Sembiring Deli Tua, Deli Serdang Regency in 2026 explores maternal health issues in Indonesia, highlighted by high Maternal Mortality Rates (MMR). It examines recovery challenges after Caesarean sections, such as infection, uterine rupture, bleeding, and delayed recovery. Early mobilization, or moving shortly after delivery, is suggested to support recovery. Using a quasi-experimental design with pre-test and post-test, the study finds that early mobilization significantly improves uterine involution (Wilcoxon signed-rank test: Z = -2.985, p = 0.03).